3.2x+4.5x+3-2=-2.2x+5x-7

Simple and best practice solution for 3.2x+4.5x+3-2=-2.2x+5x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.2x+4.5x+3-2=-2.2x+5x-7 equation:


Simplifying
3.2x + 4.5x + 3 + -2 = -2.2x + 5x + -7

Reorder the terms:
3 + -2 + 3.2x + 4.5x = -2.2x + 5x + -7

Combine like terms: 3 + -2 = 1
1 + 3.2x + 4.5x = -2.2x + 5x + -7

Combine like terms: 3.2x + 4.5x = 7.7x
1 + 7.7x = -2.2x + 5x + -7

Reorder the terms:
1 + 7.7x = -7 + -2.2x + 5x

Combine like terms: -2.2x + 5x = 2.8x
1 + 7.7x = -7 + 2.8x

Solving
1 + 7.7x = -7 + 2.8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2.8x' to each side of the equation.
1 + 7.7x + -2.8x = -7 + 2.8x + -2.8x

Combine like terms: 7.7x + -2.8x = 4.9x
1 + 4.9x = -7 + 2.8x + -2.8x

Combine like terms: 2.8x + -2.8x = 0.0
1 + 4.9x = -7 + 0.0
1 + 4.9x = -7

Add '-1' to each side of the equation.
1 + -1 + 4.9x = -7 + -1

Combine like terms: 1 + -1 = 0
0 + 4.9x = -7 + -1
4.9x = -7 + -1

Combine like terms: -7 + -1 = -8
4.9x = -8

Divide each side by '4.9'.
x = -1.632653061

Simplifying
x = -1.632653061

See similar equations:

| 5+x(x-4)=37 | | 4y+9x+3=7+9x | | 2y=y+10 | | 2e^3x+6=32 | | 15/15-12/12 | | 4p-2c-2p+8c= | | sen(5x)=0 | | 3x+2y=8.75 | | I-20=-23 | | 0=30x-16x^2 | | 23/24-11/12 | | 15x(8-5)= | | 6=n/2 | | 9x^2-3x+4=15-x | | 9x^2-3x+4=15x | | in(2x-5)+3=9 | | 16t^2-54t-7=0 | | n=3.75*4 | | 12=16t^2+24t+3 | | 2x^2-y^2=8solvey | | 16x^4+8x^2+3=0 | | 27+n=42 | | 2x^2+3x+1.125=0 | | -8n=120 | | 3x^2+27x=-18 | | 3x+3+5x=83 | | 3a^-4/3/7b^-1/3 | | 2=2/2(2)+b | | 25/100=n/124 | | 2x+8-x=-7 | | .04x=280 | | B-17=15 |

Equations solver categories